Model Six Sigma Untuk Mengurangi Produk Cacat Karena Faktor Ketidakhalalan - Pahlawan, Firman Mega; Vanany, Iwan (Muhammadiyah University Press, 2019)
In recent years, the halal food issue is an interesting for researchers and practitionaires. Halal food market was growing significantly and food industries are becoming more aware of halal food improvement and certification. The food industries need to follow the rules of halal assurance system for the halal institution regulation. The purpose of this paper is proposesix sigma model for product defect reduction in halal food. The four steps are used to reduce halal product defect such as (1) Define, (2) Measure, (3) Analyze, and (4) Improve. Several tools are used in proposed model such as brainstorming, pareto diagram, RCA whys and others. The proposed six sigma model is applied in chicken slaughtering industry as case study in this research. There are types of product defect due to non-halal factor, such as (1) chicken do not pass antemortem checks result, (2) chicken die before slaughtering, (3) the slaughter process is not done by cutting off 3 channels at once (blood vessels, trachea, and esophagus), (4) the meat produced is not suitable for consumption (not toyyib). Based on processing stage, the biggest loss occurs at the meat processing stage, which is due to the quality of chicken meat are not toyyib. Based on each component of costs, the biggest loss occurs in the component of raw material costs.